Tricuspid regurgitation after successful mitral valve surgery - Katsi, Vasiliki (Oxford University Press, 2012)
The tricuspid valve (TV) is inseparably connected with the mitral valve (MV) in terms of function. Any pathophysiological condition concerning the MV is potentially a threat for the normal function of the TV as well. One of the most challenging cases is functional tricuspid regurgitation (TR) after surgical MV correction. In the past, TR was considered to progressively revert with time after left-sided valve restoration. Nevertheless, more recent studies showed that TR could develop and evolve postoperatively over time, as well as being closely associated with a poorer prognosis in terms of morbidity and mortality. Pressure and volume overload are usually the underlying pathophysiological mechanisms; structural alterations, like tricuspid annulus dilatation, increased leaflet tethering and right ventricular remodelling are almost always present when regurgitation develops. The most important risk factors associated with a higher probability of late TR development involve the elderly, female gender, larger left atrial size, atrial fibrillation, right chamber dilatation, higher pulmonary artery systolic pressures, longer times from the onset of MV disease to surgery, history of rheumatic heart disease, ischaemic heart disease and prosthetic valve malfunction. The time of TR manifestation can be up to 10 years or more after an MV surgery. Echocardiography, including the novel 3D Echo techniques, is crucial in the early diagnosis and prognosis of future TV disease development. Appropriate surgical technique and timing still need to be clarified.